Progressive Taxation and Monetary Policy in a Currency Union - Wolfgang Strehl; Philipp Engler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyse the welfare properties of progressive income taxes in a stylized DSGE model of a currency union calibrated to the Eurozone. When the central bank follows a standard Taylor rule and volatility originates solely in productivity shocks, we find that considerable welfare gains can be achieved by introducing a progressive income tax schedule. The reason is that the slightly lower average levels of consumption and greater volatility of hours are more than offset in their effects on welfare by a significant reduction in consumption volatility. However, at the aggregate level this result is not robust to the introduction of rule-of-thumb households, but we find a positive welfare effect for the latter type of households while intertemporally optimizing households lose. Furthermore, under an optimal monetary policy, welfare falls even in the absence of rule-of-thumb households. When demand shocks are considered, progressive taxes cannot improve welfare. Increasing tax progression above the Eurozone average is a "beggar-thyself" policy for all specifications.
Keywords: F45; E62; E52; 330